Analisis Pengaruh Brand Identity, Brand Image, Brand Interaction, dan Brand Personality Terhadap Customer Satisfaction dan Pengaruhnya Terhadap Repurchase Intention Pada Kosmetik Merek Lokal di Kota Batam - Erilia Kesumahati; Selly Novianti (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
This study aimed to determine whether there are significant effect of brand identity, brand image, brand interaction, brand personality and customer satisfaction on repurchase intention of local brand cosmetics in Batam City. This study used 279 respondents using purposive sampling method, only respondents who had bought local brand cosmetics in Batam City were the respondents in this study This study used SPSS version 26.0 program for analysis of respondents' demographic data and then continued with testing using the SmartPLS version 3.0 program for analysis of the relationship between variables. Based on the results of hypothesis testing, data showed that brand image, brand interaction, and brand personality have significant positive effect on customer satisfaction. Meanwhile, brand identity has no significant positive effect on customer satisfaction. In addition, customer satisfaction has been shown to have a significant positive effect on repurchase intention. Based on the results of this study, in increasing repurchase intention for local brand cosmetics, it is recommended that local brand cosmetics business people be able to increase customer satisfaction first through the creation of a good brand image, brand interaction, and brand personality